Radar girls eaudiobook - Ackerman, Sara (2021)
"A fresh, delightful romp of a novel."—Kate Quinn, New York Times bestselling author of The Rose Code * SheReads Most Anticipated Historical Fiction of Summer 2021 pick * Book Reporter Summer Reading pick * BiblioLifestyle Most Anticipated Summer 2021 Historical Fiction Books selection * Greatist Best Historical Fiction Books pick * An extraordinary story inspired by the real Women's Air Raid Defense, where an unlikely recruit and her sisters-in-arms forge their place in WWII history. Daisy Wilder prefers the company of horses to people, bare feet and salt water to high heels and society parties. Then, in the dizzying aftermath of the attack on Pearl Harbor, Daisy enlists in a top secret program, replacing male soldiers in a war zone for the first time. Under fear of imminent invasion, the WARDs guide pilots into blacked-out airstrips and track unidentified planes across Pacific skies. But not everyone thinks the women are up to the job, and the new recruits must rise above their differences and work side by side despite the resistance and heartache they meet along the way. With America's future on the line, Daisy is determined to prove herself worthy. And with the man she's falling for out on the front lines, she cannot fail. From radar towers on remote mountaintops to flooded bomb shelters, she'll need her new team when the stakes are highest. Because the most important battles are fought—and won—together. This inspiring and uplifting tale of pioneering, unsung heroines vividly transports the reader to wartime Hawaii, where one woman's call to duty leads her to find courage, strength and sisterhood. "A wow of a book...[that is] a captivating story of friendship, heartbreak and true love. Highly recommend!" —Karen Robards, New York Times bestselling author of The Black Swan of Paris